Identidade pessoal em Hume e em Kant - Peixoto, Cristiano Rodrigues (2016)
The issue of this dissertation is the problem of personal identity. More specifically, the objective of this work is to investigate and compare how Hume and Kant construct, within their own philosophical systems, their theories of personal identity (of the self), so that these theories can set the grounds for the construction of theoretical knowledge. Hume’s theory of personal identity is closely connected to his empirical model of investigation, according to which no metaphysical conclusion can be accepted. This implies a very specific limitation to the humean description of personal identity. Because he can’t find a safe empirical reference for the self, Hume is obliged to describe it as a mere fiction, which the imagination creates to try to give unity to the set of perceptions that composes the mind. Kant, on the other hand, constructs his theory of the self with the aim of explaining the possibility of the a priori knowledge in Mathematics and in Physics. Kant tries to find which attributes must necessarily belong to the self so that this self can be, at the same time, the a priori transcendental condition of a subjectivity in general and the equally a priori transcendental condition for the construction of objective knowledge. Moreover, Kant shows the impossibility of objectively knowing, as intuition, the self, and limits himself to the description of the self as a mere subjective consciousness of the synthetic capacities of the understanding. Several disparities, thus, can be perceived between the theories of personal identity of these two authors. Based on these differences, the present work also examines the possibility of making an interpretation of the humean theory of the self by using elements of the kantian philosophy. The purpose of this kind of interpretation is to propose a solution to the difficulties faced by Hume in the description of his theory of personal identity.